Parental Responses to Children's Achievement Test Results - Deborah A. Cobb-Clark; Tiffany Ho; Nicolás Salamanca (Institute of Labor Economics (IZA), 2021)
We use quasi-experimental variation in the timing of national standardized test-score reports to estimate the causal impact of giving parents objective information about children's academic achievement. Releasing test scores leads to more modest perceptions of academic achievement and reduced school satisfaction. The use of private tutoring is increased, while extracurricular activities are reduced. Examining the underlying mechanisms, we show that is it public-school parents and parents of children receiving unexpectedly "bad" test scores who alter their perceptions. Learning that a child scores above the national average raises perceived academic achievement and time devoted to education, while reducing leisure time.
Keywords: I21; J13; D10; D90; 330; parental investments; test-score information; parental perceptions; overconfidence